Topics at the frontier of statistics and network analysis : (re)visiting the foundations - Kolaczyk, Eric D. (Cambridge : Cambridge University Press, 2017)
This snapshot of the current frontier of statistics and network analysis focuses on the foundational topics of modeling, sampling, and design. Primarily for graduate students and researchers in statistics and closely related fields, emphasis is not only on what has been done, but on what remains to be done.
1. Background and overview -- 2. Network modeling -- 3. Sampling networks -- 4. Networked experiments -- 5. Emerging topic areas -- Appendix background on graphs.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: System analysis -- Statistical methods; Network analysis (Planning) -- Statistical methods; Statistics